Excess demand and investment in the United Kingdom - Williams, B. R. (Statistical and Social Inquiry Society of Ireland, 1948)
By excess demand I mean the current excess of private disposable income, after the deduction of voluntary saving, over the target- figure for the supply of consumption goods at current prices, and that piled-up demand for war-time arrears of semi-durable goods and maintenanceof equipment which is backed by savings in liquid form.
Read before the Society, 23 April 1948
Keywords: Excess demand, United Kingdom; Investment, United Kingdom; Business cycles; Inflation; 314.15